2017
DOI: 10.1016/j.quascirev.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Coastal lake sediments reveal 5500 years of tsunami history in south central Chile

Abstract: We present an exceptionally long and continuous coastal lacustrine record of ~5500 years from Lake Huelde on the west coast of Chiloé Island in south central Chile. The study area is located within the rupture zone of the giant AD 1960 Great Chilean Earthquake (M W 9.5). The subsequent earthquake-induced tsunami inundated Lake Huelde and deposited mud rip-up clasts, massive sand and a mud cap in the lake. Long sediment cores from 8 core sites within Lake Huelde reveal 16 additional sandy layers in the 5500 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 60 publications
6
107
0
2
Order By: Relevance
“…Since the northern part of the Valdivia segment is currently locked (Moreno et al, 2011), maximal slip is expected in the north, as was the case during the 1960 Great Chilean earthquake. (Kempf et al, 2017) and to a turbidite in Lake Riñihue (1,929-2,103 cal years B.P.) However, should a large amount of slip occur at the latitude of Aysén Fjord, an intensity of VII½-VIII could be regarded as a maximum seismic intensity in the fjord for subduction earthquakes in accordance with observations by Van Daele et al (2015), where this value is reported for the largest earthquake on record.…”
Section: Megathrust Earthquakessupporting
confidence: 82%
See 2 more Smart Citations
“…Since the northern part of the Valdivia segment is currently locked (Moreno et al, 2011), maximal slip is expected in the north, as was the case during the 1960 Great Chilean earthquake. (Kempf et al, 2017) and to a turbidite in Lake Riñihue (1,929-2,103 cal years B.P.) However, should a large amount of slip occur at the latitude of Aysén Fjord, an intensity of VII½-VIII could be regarded as a maximum seismic intensity in the fjord for subduction earthquakes in accordance with observations by Van Daele et al (2015), where this value is reported for the largest earthquake on record.…”
Section: Megathrust Earthquakessupporting
confidence: 82%
“…However, should a large amount of slip occur at the latitude of Aysén Fjord, an intensity of VII½-VIII could be regarded as a maximum seismic intensity in the fjord for subduction earthquakes in accordance with observations by Van Daele et al (2015), where this value is reported for the largest earthquake on record. Combined with the presence of tsunami deposits in the southern part of the segment (Kempf et al, 2017) and our SL-EF, we infer this to be an (exceptional) earthquake with a large amount of slip in the southern part of the Valdivia segment and less slip in the northern part. We can thus readily expect widespread offshore-originating small-scale MTDs for a megathrust earthquake with high slip (> 30 m) in the southern part of the Valdivia segment.…”
Section: Megathrust Earthquakesmentioning
confidence: 66%
See 1 more Smart Citation
“…Another similar approach was used by Kempf et al . () in lakes in Chile, where the application of geophysical data to establish long‐term recurrence intervals of tsunamigenic events was successful.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…These tests allow the evaluation of the local static ground water level, the atmospheric pressure and the hydrostatic pressure for various depths of the dissipation test. Based on these three parameters, the actual P inj is calculated as; P inj = P total À (P hydro + P atm ) (K€ orber et al, 2009;McCall et al, 2014;Geoprobe, 2015). The estimated hydraulic conductivity (K est. )…”
Section: Direct Push In Situ Techniquesmentioning
confidence: 99%